Is Dapagliflozin future for CKD? - Yumna Zafar; Yusra Iqbal; Syeda Sanila Aijaz (Journal of the Pakistan Medical Association, 2022)
Dapagliflozin belongs to the latest class of anti-diabetic medication Sodium-glucose co-transporter two inhibitors (SGLT2i). The drug is mainly used in type 2 diabetes (T2D) by preventing the reabsorption of glucose in the proximal tubule of the kidney causing glycosuria and regulating blood glucose levels. It is a well-tolerated drug with rare side effects including hypoglycemia, diabetic ketoacidosis, genital and urinary tract infections. The drug gain popularity through its effect in lowering cardiovascular and renal events in patients with T2D through mechanisms independent of lowering blood glucose levels. (1) Adding to its benefits, Wheeler et al stated that Dapagliflozin decreases the risk of renal and cardiovascular events and reduces overall mortality in diabetic and non-diabetics with chronic kidney disease (CKD). Reduction in non-cardiovascular deaths was the critical factor to improve the mortality rates, most common among which were infections and malignancies. (3) Another 2021 publication of the European Heart Journal also showed that Dapagliflozin significantly reduces mortality in patients suffering from CKD with or without type 2 diabetes. Reduction in non-cardiovascular deaths was the key factor in improving the mortality rates, most common among which were infections and malignancies. (4) The prevalence of CKD in South Asian countries is relatively high. Pakistan tops the list with the highest prevalence of 21.2%. (4) Dapagliflozin has been approved for use in Pakistan in the year 2017.(5) Also, the more compelling pieces of evidence and greater recognition of CKD, and greater use of SGLT2 inhibitors in non-diabetics in clinical practice are imperative for the many people who stand to benefit from longer and healthier lives. The drug is opening new horizons for the treatment of CKD. Continue..